Roosevelt's second act : the election of 1940 and the politics of war - Moe, Richard (Pivotal moments in American history., 2013)
""In Roosevelt's Second Act Richard Moe has shown in superb fashion that what might seem to have been an inevitable decision of comparatively little interest was far from it.""--David McCullough On August 31, 1939, nearing the end of his second and presumably final term in office, President Franklin Delano Roosevelt was working in the Oval Office and contemplating construction of his presidential library and planning retirement. The next day German tanks had crossed the Polish border; Britain and France had declared war. Overnight the world had changed, and FDR found himself being forced to c